Preparation method and application of polyether polyol for flame composite sponge

Through the chemical reactions of phenolic substances with benhydish and epoxyl oxylene, the pose polyether is prepared to solve the environment and performance problems of existing sponge bonding methods, and the flame composite sponge of high performance, environmental protection and economy is achieved.

CN115584021BActive Publication Date: 2025-01-24JIANGSU ZHONGSHAN NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211291827.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2025-01-24
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

The existing sponge bonding methods use glue, which leads to unfriendly environment and stiff and easy to damage on the bonding surface, which cannot meet the needs of high comfort and long life. At the same time, existing flame composites and flame retardants have safety and cost issues.

Method used

Using phenolic substances as initiators, through esterification of phthalic anhydride and ring-opening polymerization of alkylene oxide, a polyether for flame composite sponges with good compatibility with the basic polyether of polyurethane soft foam was prepared.

Benefits of technology

The flame composite sponge is environmentally friendly, has strong adhesion, is low in cost, has no toxic and harmful substances spilling after burning, and has high adhesion and high tear strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003899787280000061
    Figure BDA0003899787280000061
Patent Text Reader

Abstract

The present invention provides a method for preparing polyether polyols, and relates to the technical field of chemical industry. The method for preparing polyether polyols comprises the step of polymerizing an initiator and an alkylene oxide under the catalysis of a catalyst to form polyether polyols; the catalyst is a carrier ZSM-5 loaded with MgO and TiO2. The method for preparing polyether polyols of the present invention can be used repeatedly for preparing EO-terminated polyether polyols, and the refining and neutralization steps are reduced, thereby reducing the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a preparation method and application of polyether polyol for flame composite sponge, belonging to the field of polymer materials. Background Art

[0002] Polyurethane soft foam has a wide range of hardness and density and has been widely used in the fields of car seat cushions, home furnishings, packaging materials, etc. With the improvement of living standards, in order to improve the comfort of use, sponges are usually bonded to fabrics, or two different types of sponges are bonded to achieve better performance. However, the existing general bonding is through glue, which volatilizes and gels to produce VOCs during the bonding process, which is not environmentally friendly, and the bonded surface formed is rigid and easily damaged, which reduces comfort and service life.

[0003] There are also methods of adding flame compounding agents or flame retardants to ordinary sponges to make the foam achieve a flame compounding effect. However, flame retardants are easy to diffuse at high temperatures, and flame retardants containing halogens decompose to produce toxic gases after combustion, so their use has been restricted. Flame compounding agents are expensive and have poor miscibility with polyethers or isocyanates, which is not conducive to the production of combined polyethers, which also limits their use. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a polyether polyol for a flame composite sponge. The obtained polyether polyol can be used to prepare a flame composite sponge. The polyether polyol has good compatibility with a polyurethane soft foam base polyether, is environmentally friendly, has strong bonding strength, and is low in cost.

[0005] The purpose of the present invention is achieved by adopting the following technical scheme.

[0006] A method for preparing polyether for flame composite sponge comprises taking phenolic substances as initiators, adding phthalic anhydride for esterification, and then ring-opening polymerization with alkylene oxide under the action of a catalyst to obtain the polyether for flame composite sponge.

[0007] In the present invention, the phenolic substance is one or more of bisphenol A, bisphenol A type polyether polyol, bisphenol fluorene and bisphenol fluorene type polyether polyol.

[0008] In the present invention, the molar ratio of the phenol initiator to phthalic anhydride is 2-2.1:1, and the esterification temperature is 140-180°C.

[0009] In the present invention, the catalyst is one or more of a bimetallic complex, boron trifluoride etherate, dodecanamine, and an alkali metal; the polymerization temperature of the epoxyalkane is 80° C.-160° C., and the reaction pressure does not exceed 0.4 MPa.

[0010] In the present invention, the amount of the catalyst added is 0.003%-1% of the sum of the mass of the phenolic substance, phthalic anhydride and alkylene oxide.

[0011] In the present invention, the number average molecular weight of the polyether used for the flame composite sponge is 1500-6000.

[0012] The present invention also provides the use of the polyether in preparing a flame composite sponge, comprising the following steps:

[0013] (1) at 20-30° C., 3-25 parts by weight of the flame composite sponge polyether according to any one of claims 1-6, 75-100 parts by weight of common soft foam polyether, 0.3-2 parts by weight of a catalyst, 0.5-15 parts by weight of water, 0.5-10 parts by weight of a foam leveling agent and 0-50 parts by weight of a physical foaming agent are mixed and stirred uniformly;

[0014] (2) adding 30-100 parts by weight of polyisocyanate to the mixture obtained in step (1), stirring, foaming, and aging to obtain the flame composite sponge.

[0015] In the present invention, the polyisocyanate in step (2) is one or a mixture of two or more of toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated phenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.

[0016] In the present invention, the catalyst is at least one of A1, A33, triethylenediamine, triethanolamine, ethanolamine, diethanolamine, ethylenediamine, dimethylethanolamine, N,N-dimethylcyclohexylamine, stannous octoate, dibutyltin dilaurate, zinc isooctanoate, bismuth isooctanoate, and tetrabutyl titanate.

[0017] In the present invention, the foam leveling agent is one or a mixture of two or more of polyether modified silicone surfactants, silicones, alkyl alcohol amides, and fatty alcohol polyoxyethylene ether surfactants; the foam leveling agent is preferably one or a mixture of two or more of L580 of Momentive Company of the United States and DC-5810 of Air Products and Chemicals Co., Ltd. of the United States; the physical foaming agent is one or a mixture of several of dichloromethane, liquid carbon dioxide, n-pentane, cyclopentane, isopentane or petroleum ether.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The polyether for flame composite sponge prepared by the present invention has good compatibility with the polyether for common soft foam and can be stored for a long time as a combined polyether.

[0020] (2) The flame composite sponge prepared by the present invention uses polyether to replace flame composite agents and flame retardants, and can make the sponge melt without carbonization after combustion, which is beneficial to the adhesion of materials. It is halogen-free, no toxic or harmful substances overflow during combustion, and is environmentally friendly.

[0021] (3) The flame composite sponge prepared by the present invention is easy to operate, and the bonding surface is not easy to fall off, and has high bonding and high tear strength. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with embodiments, but they do not limit the implementation of the present invention.

[0023] Sources of reagents used in the present invention: Catalyst A33 is an amine catalyst, produced by American Momentive Company, and is a liquid containing 33% (mass percentage) triethylenediamine. Catalyst T9 is stannous octoate, produced by Henry Polymer Materials Co., Ltd. DMC catalyst is produced by Huai'an Bader Polyurethane Co., Ltd. BPA-10 is a bisphenol A polyether polyol with a number average molecular weight of 800 produced by Jiangsu Zhongshan New Materials Co., Ltd. BPF-15 is a bisphenol fluorene polyether polyol with a number average molecular weight of 1000 produced by Jiangsu Zhongshan New Materials Co., Ltd. Soft foam polyether ZS-2802 is a glycerol polyether polyol with a number average molecular weight of 3000 produced by Jiangsu Zhongshan New Materials Co., Ltd.

[0024] Example 1 Preparation of flame composite sponge 1

[0025] The flame composite sponge 1 was prepared by the following method:

[0026] (1) 228 g of bisphenol A and 74 g of phthalic anhydride were added to a reaction kettle. After the kettle was replaced with nitrogen, the vacuum was evacuated to a vacuum degree of -0.095 MPa, the temperature was raised to 150° C., and an esterification reaction was carried out at 150° C. The esterification reaction time was 3 h. After the esterification reaction was completed, a sample was taken to measure the acid value, and the acid value was <1 mgKOH / g at this time; the temperature was lowered to 60° C., 0.08 g of DMC catalyst was added, the kettle was replaced with nitrogen, the vacuum was evacuated to a vacuum degree of -0.095 MPa, the temperature was raised to 140° C., the vacuum pump was turned off, and 900 g of propylene oxide was added dropwise. During the dropwise addition, the reaction temperature was controlled to be 140° C., and the reaction pressure was controlled not to exceed 0.4 MPa; after the dropwise addition was completed, the reaction was continued at 140° C. until the pressure no longer changed, the vacuum was evacuated to a vacuum degree of -0.095 MPa, and the vacuum degree was maintained for 0.5 h; the temperature was lowered to 80° C., and the material was discharged to obtain polyether a for flame composite sponge.

[0027] (2) At 25°C, 20 parts by weight of flame composite sponge polyether a, 80 parts by weight of soft foam polyether ZS-2802, 3.5 parts by weight of water, 1.0 parts by weight of foam leveler L580 (Momentive, USA), 0.3 parts by weight of catalyst A33 and 0.2 parts by weight of catalyst T9 were mixed and stirred evenly to obtain mixture A1. 50 parts by weight of TDI80 (Cangzhou Dahua Co., Ltd.) were added to mixture A1 and stirred at high speed. After the material turned slightly white, it was quickly poured into the prepared mold so that the foam filled the mold, and then allowed to stand for 30 minutes, and then placed in a 50°C oven for aging for 1 hour, cooled and demolded, and flame composite sponge 1 was obtained.

[0028] Example 2 Preparation of flame composite sponge 2

[0029] Flame composite sponge 2 was prepared by the following method:

[0030] (1) 800 g of polyether BPA-10 and 72 g of phthalic anhydride were added to a reaction kettle. After the kettle was replaced with nitrogen, the vacuum was evacuated to a vacuum degree of -0.095 MPa. The temperature was raised to 155° C. and an esterification reaction was carried out at 155° C. for 3 h. After the esterification reaction was completed, a sample was taken to measure the acid value. At this time, the acid value was <1 mgKOH / g. After the temperature was lowered to 60° C., 0.12 g of DMC catalyst was added. After the kettle was replaced with nitrogen, the vacuum was evacuated to a vacuum degree of -0.095Mpa, heat to 145°C, turn off the vacuum pump, and drop a mixture of 1000g propylene oxide and 350g ethylene oxide. During the dropwise addition, control the reaction temperature to 145°C and control the reaction pressure not to exceed 0.4Mpa; after the dropwise addition is completed, continue the reaction at 145°C until the pressure no longer changes, then evacuate to a vacuum degree of -0.095Mpa, and maintain the vacuum degree for 0.5h; cool to 80°C and discharge to obtain polyether b for flame composite sponge.

[0031] (2) At 25°C, 20 parts by weight of flame composite sponge polyether b, 80 parts by weight of soft foam polyether ZS-2802, 3.5 parts by weight of water, 1.2 parts by weight of foam leveler L580 (Momentive, USA), 0.5 parts by weight of catalyst A33 and 0.3 parts by weight of catalyst T9 were mixed and stirred evenly to obtain mixture A2. 45 parts by weight of TDI80 (Cangzhou Dahua Co., Ltd.) were added to mixture A2 and stirred at high speed. After the material turned slightly white, it was quickly poured into the prepared mold so that the foam filled the mold, and then allowed to stand for 30 minutes, and then placed in a 50°C oven for aging for 1 hour, cooled and demolded, and flame composite sponge 2 was obtained.

[0032] Example 3 Preparation of flame composite sponge 3

[0033] The flame composite sponge 3 was prepared by the following method:

[0034] (1) 800g of polyether BPF-15 and 75g of phthalic anhydride were added to a reaction kettle. After the kettle was replaced with nitrogen, it was evacuated to a vacuum degree of -0.095Mpa, and the temperature was raised to 165°C. Esterification reaction was carried out at 165°C for 3h. After the esterification reaction was completed, a sample was taken to measure the acid value, and the acid value was <1mgKOH / g; the temperature was lowered to 60°C, 0.12g of DMC catalyst was added, the kettle was replaced with nitrogen, and the vacuum degree was -0.095Mpa, and the temperature was raised to 160°C. The vacuum pump was turned off and 3250g of propylene oxide was added dropwise. During the dropwise addition, the reaction temperature was controlled to be 160°C and the reaction pressure was controlled not to exceed 0.4Mpa; after the dropwise addition was completed, the reaction was continued at 160°C until the pressure no longer changed, and the vacuum degree was evacuated to a vacuum degree of -0.095Mpa, and the vacuum degree was maintained for 0.5h; the temperature was lowered to 80°C and the material was discharged to obtain polyether c for flame composite sponge.

[0035] (2) At 25°C, 25 parts by weight of flame composite sponge polyether c, 75 parts by weight of soft foam polyether ZS-2802, 3.5 parts by weight of water, 1.2 parts by weight of foam leveler L580 (Momentive, USA), 0.5 parts by weight of catalyst A33 and 0.3 parts by weight of catalyst T9 were mixed and stirred evenly to obtain mixture A3. 42 parts by weight of TDI80 (Cangzhou Dahua Co., Ltd.) were added to mixture A3 and stirred at high speed. After the material turned slightly white, it was quickly poured into the prepared mold so that the foam filled the mold, allowed to stand for 30 minutes, and then placed in a 50°C oven for aging for 1 hour, cooled and demolded, and flame composite sponge 3 was obtained.

[0036] Comparative Example 1

[0037] Preparation of control sponge 1: At 25°C, take 20 parts by weight of polyether BPA-10, 80 parts by weight of soft foam polyether ZS-2802, 3.5 parts by weight of water, 1.0 parts by weight of foam leveler L580, 0.5 parts by weight of catalyst A33 and 0.3 parts by weight of catalyst T9, mix and stir evenly to obtain mixture A4. Add 45 parts by weight of TDI80 (Cangzhou Dahua Co., Ltd.) to mixture A4, stir at high speed, and when the material turns slightly white, quickly pour it into the prepared mold so that the foam fills the mold, let it stand for 30 minutes, and then put it into a 50°C oven for 1 hour, cool and demold, and the control sponge 1 is obtained.

[0038] Comparative Example 2

[0039] Preparation of control sponge 2: At 25°C, take 20 parts of dimethyl methyl phosphate (flame retardant DMMP), 80 parts of soft foam polyether ZS-2802, 3.5 parts of water, 1.5 parts of foam leveler L580, 0.5 parts of catalyst A33 and 0.4 parts of catalyst T9, mix and stir evenly to obtain mixture A5. Add 43 parts of TDI80 (Cangzhou Dahua Co., Ltd.) to mixture A5, stir at high speed, and when the material turns slightly white, quickly pour it into the prepared mold so that the foam fills the mold, let it stand for 30 minutes, and then put it into a 50°C oven for 1 hour, cool and demold, and the control sponge 2 is obtained.

[0040] Comparative Example 3

[0041] Preparation of control sponge 3: At 25°C, take 20 parts of PS-3152 (phthalic anhydride polyester polyol from Stepan Company, hydroxyl value: 300-330 mgKOH / g), 80 parts by weight of soft foam polyether ZS-2802, 3.5 parts by weight of water, 1.1 parts by weight of foam leveler L580, 0.6 parts by weight of catalyst A33 and 0.2 parts by weight of catalyst T9, mix and stir evenly to obtain mixture A6. Add 50 parts by weight of TDI80 (Cangzhou Dahua Co., Ltd.) to mixture A6, stir at high speed, and when the material turns slightly white, quickly pour it into the prepared mold so that the foam fills the mold, let it stand for 30 minutes, then put it into a 50°C oven for aging for 1 hour, cool and demould, and control sponge 3 is obtained.

[0042] The flame composite sponges 1-3 and control sponges 1-3 prepared above were subjected to physical property tests, flame composite adhesion experiments and automobile inner lining non-woven fabric adhesion experiments, respectively.

[0043] The tensile strength of each sponge was measured according to GB / T6344-2008. The tear strength was measured according to GB / T529-2008. The density was tested according to conventional methods.

[0044] The flame composite pasting experiment of each sponge and ordinary polyurethane soft foam was carried out according to the following steps: first, the sponge to be tested was cut into strips of 100cm×10cm×10cm, and the sponge strip to be tested and the ordinary polyurethane soft foam of the same size were fixed on a flat plate (glass) respectively. The sponge strip to be tested was passed horizontally through the flame within 10s with the sponge surface facing downward to slightly melt the sponge surface, and then quickly pasted onto the ordinary polyurethane soft foam on another horizontal plate. After lightly pressing the two horizontal plates for 15 minutes, the peel strength was measured according to ISO8067-2008, and the total volatile organic matter after the sponge composite was measured according to VDA277. The preparation method of ordinary polyurethane soft foam is as follows: at 25°C, take 100 parts by weight of soft foam polyether ZS-2802, 3.5 parts by weight of water, 1.5 parts by weight of foam leveler L580, 0.5 parts by weight of catalyst A33 and 0.4 parts by weight of catalyst T9, mix and stir evenly; add 45 parts by weight of TDI80 (Cangzhou Dahua Co., Ltd.) to the above mixture, stir at high speed, and after the material turns slightly white, quickly pour it into the prepared mold to fill the mold with foam, let it stand for 30 minutes, then put it into a 50°C oven for curing for 1 hour, and cool and demold.

[0045] The flame composite pasting test of each sponge and the non-woven fabric of the automobile lining is carried out according to the following steps: first, the sponge to be tested is cut into a sample of 100cm×10cm×10cm, and the sponge sample to be tested and the non-woven fabric of the same size are fixed on a horizontal plate (glass) respectively. The sponge sample to be tested is placed with the sponge surface facing downward, and passed through the flame horizontally within 10s to slightly melt the sponge surface, and then quickly pasted on the non-woven fabric on another horizontal plate, and then the two horizontal plates are gently pressed for 5 minutes, and the peel strength is measured according to ISO8067-2008, and the total volatile organic matter after the sponge composite is measured according to VDA277.

[0046] Table 1 Comparison of sponge performance

[0047]

[0048] As can be seen from Table 1, the polyether for flame composite sponge prepared by the present invention is easy to use, has the best peel strength in the flame composite pasting experiment with ordinary polyurethane soft foam and non-woven fabric, and has a low TVOC content, and can be used in high-end fields such as automobiles and homes.

Claims

1. The application of polyether in the preparation of flame composite sponge is characterized by comprising the following steps: (1) at 20-30° C., 3-25 parts by weight of flame composite sponge polyether, 75-100 parts by weight of common soft foam polyether, 0.3-2 parts by weight of catalyst, 0.5-15 parts by weight of water, 0.5-10 parts by weight of foam leveling agent and 0-50 parts by weight of physical foaming agent are mixed and stirred uniformly; (2) adding 30-100 parts by weight of polyisocyanate to the mixture obtained in step (1), stirring, foaming, and aging to obtain the flame composite sponge; The flame composite sponge polyether is obtained by using phenolic substances as initiators, adding phthalic anhydride for esterification, and then ring-opening polymerization with alkylene oxide under the action of a catalyst; the phenolic substances are one or more of bisphenol A, bisphenol A-based polyether polyols, bisphenol fluorene and bisphenol fluorene-based polyether polyols; the molar ratio of the phenolic initiator to phthalic anhydride is 2 to 2.1:1, and the esterification temperature is 140-180°C.

2. The application according to claim 1, characterized in that: The catalyst is one or more of a bimetallic complex, boron trifluoride etherate, dodecaned tertiary amine, and an alkali metal; the polymerization temperature of the alkylene oxide is 80° C.-160° C., and the reaction pressure does not exceed 0.4 Mpa.

3. The application according to claim 2, characterized in that: The amount of the catalyst added is 0.003%-1% of the total mass of the phenolic substance, phthalic anhydride and alkylene oxide.

4. The application according to claim 3, characterized in that: The number average molecular weight of the polyether used in the flame composite sponge is 1500-6000.

5. The use according to claim 4, characterized in that The polyisocyanate in step (2) is one or a mixture of two or more of toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated phenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, hexamethylene diisocyanate and isophorone diisocyanate.

6. The use according to claim 5, characterized in that The catalyst is at least one of A1, A33, triethylenediamine, triethanolamine, ethanolamine, diethanolamine, ethylenediamine, dimethylethanolamine, N,N-dimethylcyclohexylamine, stannous octoate, dibutyltin dilaurate, zinc isooctanoate, bismuth isooctanoate, and tetrabutyl titanate.

7. The use according to claim 6, characterized in that The foam leveling agent is one or a mixture of two or more of polyether modified silicone surfactants, silicones, alkyl alcohol amides, and fatty alcohol polyoxyethylene ether surfactants; the physical foaming agent is one or a mixture of dichloromethane, liquid carbon dioxide, n-pentane, cyclopentane, isopentane, or petroleum ether.

8. The use according to claim 7, characterized in that The foam leveling agent is one of L580 from Momentive, USA, and DC-5810 from Air Products & Chemicals, Inc., USA, or a mixture of two or more thereof.

Citation Information

Patent Citations

  • Method for preparing polyether polyol for aromatic coating

    CN104072745A